2021
DOI: 10.1051/0004-6361/202038804
|View full text |Cite
|
Sign up to set email alerts
|

The LOFAR Two-meter Sky Survey: Deep Fields Data Release 1

Abstract: The Low Frequency Array (LOFAR) is an ideal instrument to conduct deep extragalactic surveys. It has a large field of view and is sensitive to large-scale and compact emission. It is, however, very challenging to synthesize thermal noise limited maps at full resolution, mainly because of the complexity of the low-frequency sky and the direction dependent effects (phased array beams and ionosphere). In this first paper of a series, we present a new calibration and imaging pipeline that aims at producing high fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 164 publications
(85 citation statements)
references
References 78 publications
(73 reference statements)
0
85
0
Order By: Relevance
“…The data-reduction procedure includes the correction for the direction-independent and direction-dependent effects that are caused by the instrument and the ionosphere. We make use of the latest version of the pipelines PREFACTOR 4 (van Weeren et al 2016a; Williams et al 2016;de Gasperin et al 2019) and ddf-pipeline 5 (Tasse 2014a,b;Smirnov & Tasse 2015;Tasse et al 2018Tasse et al , 2021 for the directionindependent and direction-dependent calibration, respectively. The flux scale of the LOFAR data is calibrated according to the Scaife & Heald (2012) scale using the 3C 196 model that has a total flux density of 83.1 Jy at 150 MHz.…”
Section: Lofarmentioning
confidence: 99%
“…The data-reduction procedure includes the correction for the direction-independent and direction-dependent effects that are caused by the instrument and the ionosphere. We make use of the latest version of the pipelines PREFACTOR 4 (van Weeren et al 2016a; Williams et al 2016;de Gasperin et al 2019) and ddf-pipeline 5 (Tasse 2014a,b;Smirnov & Tasse 2015;Tasse et al 2018Tasse et al , 2021 for the directionindependent and direction-dependent calibration, respectively. The flux scale of the LOFAR data is calibrated according to the Scaife & Heald (2012) scale using the 3C 196 model that has a total flux density of 83.1 Jy at 150 MHz.…”
Section: Lofarmentioning
confidence: 99%
“…To improve quality and sample size in studying the radio spectral properties at both low and high frequency, observations with similar spatial resolutions and high sensitivity at multiple frequencies are essential. The recently released high-sensitivity lowfrequency (< 150 MHz) data from the Low Frequency Array (LO-FAR) large surveys (e.g., de Gasperin et al 2021;Tasse et al 2021;Sabater et al 2021) and the undergoing joint project, SuperMIGH-TEE, which combines the MeerKAT and uGMRT telescopes to observe the MIGHTEE survey regions at 0.5-2.7 GHz with the same angular resolution (∼ 5 ′′ ) and similar sensitivity, will dramatically advance the studies of the radio spectrum.…”
Section: Limitationsmentioning
confidence: 99%
“…The third source, ILT J125453.46+542923.4, was initially included because its elongated morphology in the LoTSS DR1 images suggested that this was a genuine GSJ. However, subsequent improvements to the LoTSS image processing pipeline, included in the DR2 release (Tasse et al 2021), no longer showed the elongated radio emission so that we no longer consider this source to be a genuine GSJ. The VLA data (see Figure 2) confirmed that this is not a genuine GSJ.…”
Section: Sample Selectionmentioning
confidence: 99%